2012
DOI: 10.1016/j.radonc.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

FAZA PET/CT hypoxia imaging in patients with squamous cell carcinoma of the head and neck treated with radiotherapy: Results from the DAHANCA 24 trial

Abstract: This study emphasizes the role of FAZA PET/CT imaging as a suitable assay with prognostic potential for detection of hypoxia in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(204 citation statements)
references
References 34 publications
4
194
0
6
Order By: Relevance
“…Reischl et al [165] , Piert et al [166] , Picchio et al [167] , Maier et al [168] , Tran et al [169] Barthel et al [187] Busk et al [170] , Mortensen et al [171] , Piert et al [166] , Tran et al [169] Barthel et al [187] Busk et al [170] , Busk et al [172] , Busk et al [173] , Busk et al [174] , Busk et al [175] , Graves et al [176] , Maier et al [168] , Solomon et al [177] NA Belloli et al [178] , Picchio et al [167] , Troost et al [179] , Valtorta et al [143] NA Sorger et al [57] , Piert et al [166] , Reischl et al [165] Rasey et al [188] Postema et al [180] , Bollineni et al [181] , Trinkaus et al [58] , Verwer et al [59] NA Grosu et al [182] , Souvatzoglou et al [183] , Schuetz et al [184] , Shi et al [106] , Mortensen et al [185] , Havelund et al [186] NA…”
Section: F]ef5mentioning
confidence: 99%
“…Reischl et al [165] , Piert et al [166] , Picchio et al [167] , Maier et al [168] , Tran et al [169] Barthel et al [187] Busk et al [170] , Mortensen et al [171] , Piert et al [166] , Tran et al [169] Barthel et al [187] Busk et al [170] , Busk et al [172] , Busk et al [173] , Busk et al [174] , Busk et al [175] , Graves et al [176] , Maier et al [168] , Solomon et al [177] NA Belloli et al [178] , Picchio et al [167] , Troost et al [179] , Valtorta et al [143] NA Sorger et al [57] , Piert et al [166] , Reischl et al [165] Rasey et al [188] Postema et al [180] , Bollineni et al [181] , Trinkaus et al [58] , Verwer et al [59] NA Grosu et al [182] , Souvatzoglou et al [183] , Schuetz et al [184] , Shi et al [106] , Mortensen et al [185] , Havelund et al [186] NA…”
Section: F]ef5mentioning
confidence: 99%
“…In a multi-institutional study on 397 patients with locally advanced HNSCC, Nordsmark and colleagues found that pretreatment tumor oxygenation is a highly significant prognostic factor for survival after primary radiotherapy applied alone or combined with chemotherapy, surgery, or radiation sensitizers (12). In recent years, hypoxia detection using [(18F)]-fluoroazomycin arabinoside (FAZA) PET/CT and [(18F)]-fluoromisonidazole (FMISO) PET/CT imaging have been found to have a prognostic potential in HNSCC (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The 26-gene classifier by Eustace and colleagues, that is based on this metagene signature (18), has been shown to predict the benefit from hypoxia-modifying treatment in laryngeal cancer (16). However, as the gene classifiers are based on the measurement of hypoxia-induced gene expression and not on hypoxia itself, the classification by the gene signature does not necessarily correlate with hypoxia assessed by PET (13,19).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imaging may be able to identify spatial patterns of radioresistance, which can be used to guide and shape the dose distribution. Indirect evidence of this principle comes from studies that have found molecular imaging biomarkers to correlate with patient outcome after radiation therapy (60,61). Possible biologic targets include tumor hypoxia (measured with PET hypoxia radiotracers or with dynamic contrast-enhanced [DCE] MRI), cellularity (measured with 18 F-FDG PET or DW MRI), and others.…”
Section: Tumor Boostingmentioning
confidence: 99%